Learning to program with Visual Basic - McKeown, Patrick G. (New York ; Chichester : John Wiley and Sons, 1998)
This book is about: Using visual basic to create a first project; The selection process in visual basic; Working with arrays in visual basic; ...
Keywords: Microsoft Visual Basic; Computer program language; Microsoft Visual BASIC; BASIC (Computer program language)